Attachment states of mind among internationally adoptive and foster parents. (12th April 2017) - Raby, K. Lee; Yarger, Heather A.; Lind, Teresa; Fraley, R. Chris; Leerkes, Esther; Dozier, Mary
Abstract: The first aim of the current study was to examine the latent structure of attachment states of mind as assessed by the Adult Attachment Interview (AAI) among three groups of parents of children at risk for insecure attachments: parents who adopted internationally ( N = 147), foster parents ( N = 300), and parents living in poverty and involved with Child Protective Services (CPS; N = 284). Confirmatory factor analysis indicated the state of mind rating scales loaded on two factors reflecting adults' preoccupied and dismissing states of mind. Taxometric analyses indicated the variation in adults' preoccupied states of mind was more consistent with a dimensional than a categorical model, whereas results for dismissing states of mind were indeterminate. The second aim was to examine the degree to which the attachment states of mind of internationally adoptive and foster parents differ from those of poverty/CPS-referred parents and low-risk parents. After controlling for parental age, sex, ethnicity, and socioeconomic status, (a) internationally adoptive parents had lower scores on the dismissing dimension than the sample of community parents described by Haltigan, Leerkes, Supple, and Calkins (2014); (b) foster parents did not differ from community parents on either the dismissing or the preoccupied AAI dimension; and (c) both internationally adoptive and foster parents had lower scores on the preoccupied dimension than poverty/CPS-referred parents. Analyses using the traditional AAI categories provided convergent evidence that (a) internationally adoptive parents were more likely to be classified as having an autonomous state of mind than low-risk North American mothers based on Bakermans-Kranenburg and van IJzendoorn's (2009) meta-analytic estimates, (b) the rates of autonomous states of mind did not differ between foster and low-risk parents, and (c) both internationally adoptive and foster parents were less likely to be classified as having a preoccupied state of mind than poverty/CPS-referred parents.